Combustion characteristic inside micro channel combustor - Mohd Rosdzimin Abdul Rahman; Wan Mohd Amin Wan Shuib; Mohd Rashdan Saad; Azam Che Idris; Hasan Mohd Faizal (Penerbit Universiti Kebangsaan Malaysia, 2021)
Small-scale electronic devices require long hours’ operation and fast charging time. Potential technology to support requirement of small-scale electronic device is micro scale combustor. Unfortunately, micro scale combustion is prone to combustion instability. Therefore, objective of this study is to investigate the combustion characteristics, mechanism that stabilize the flame and combustor performance of the 2-D microchannel combustor with bluff body having various slit percentages gap. Two-dimensional computational domain with the height and length of the channel H = 1 mm and L = 16 mm is used respectively. The height of the bluff body is 0.5 mm and located at 2 mm from the inlet. The slit gap percentage varied in this study is 0% to 70%. The results show that the combustion characteristic such as stable flame, wavy flame, blow-off, and flame split into two parts is significantly influenced by the slit gap percentage. Flame is moving downstream and blow-off at the slit percentage of 10% to 25%. At the slit percentage of 30%, the flame zone moves towards the upstream due to the secondary vortex that exists behind the bluff body as slit gap increases and pushes the flame upstream. The reaction zone is split into two parts at 60% and 70% slit gap percentage. It is due to the incoming fresh mixture of CH4/air mixture flows through the slit and cuts the flame zone. It is also found that by increasing inlet velocity beyond 2.0 m/s, the flame becomes unstable and leads to blow-off as increase in equivalence ratio up to 1.0.